PERAN LINTAS CAKRAWALA DI TAMAN BACAAN MASYARAKAT (TBM) CAKRAWALA DALAM PEMBERDAYAAN MASYARAKAT BERBASIS LITERASI : STUDI EMPIRIS KECAMATAN UNGARAN BARAT KABUPATEN SEMARANG - Dias Laras Cahyaningati; Sungkowo Edy Mulyono (Jurnal Manajemen Pendidikan, 2026)
This study aims to describe the role of the Lintas Cakrawala program at the Community Reading Center (Taman Bacaan Masyarakat/TBM) Cakrawala in improving literacy and community empowerment in West Ungaran District, Semarang Regency. The research examines the forms of literacy programs, the outcomes of community empowerment, as well as the supporting and inhibiting factors in the implementation of the program. This study employs an empirical research approach with a descriptive qualitative method. Data were collected through participatory observation, in-depth interviews with TBM managers and program participants, and documentation of Lintas Cakrawala program activities. Data analysis was conducted using data reduction, data display, and conclusion drawing techniques. The results indicate that the Lintas Cakrawala program plays a significant role in increasing reading interest, community learning participation, and the development of literacy skills. The program also contributes to social and economic community empowerment through creative literacy activities and skills training in collaboration with local communities. The novelty of this research lies in the integration of literacy, skills development, and community empowerment based on local wisdom in a participatory and sustainable manner, which differs from previous studies that emphasized literacy programs solely as educational facilities.